Investigating the Formation Process of Sn-Based Lead-Free Nanoparticles with a Chemical Reduction Method. (26th February 2013) - Zhang, Weipeng; Zhao, Bingge; Zou, Changdong; Zhai, Qijie; Gao, Yulai; Acquah, Steve F. A.
Abstract : Nanoparticles of a promising lead-free solder alloy (Sn3.5Ag (wt.%, SnAg) and Sn3.0Ag0.5Cu (wt.%, SAC)) were synthesized through a chemical reduction method by using anhydrous ethanol and 1, 10-phenanthroline as the solvent and surfactant, respectively. To illustrate the formation process of Sn-Ag alloy based nanoparticles during the reaction, X-ray diffraction (XRD) was used to investigate the phases of the samples in relation to the reaction time. Different nucleation and growth mechanisms were compared on the formation process of the synthesized nanoparticles. The XRD results revealed different reaction process compared with other researchers. There were many contributing factors to the difference in the examples found in the literature, with the main focus on the formation mechanism of crystal nuclei, the solubility and ionizability of metal salts in the solvent, the solid solubility of Cu in Ag nuclei, and the role of surfactant on the growth process. This study will help define the parameters necessary for the control of both the composition and size of the nanoparticles.